The Best American Newspaper Narratives, Volume 7 - Reaves, Gayle, 1958- (Mayborn best American newspaper narrative series ;, 2020)
This anthology collects the winners of the 2019 Best American Newspaper Narrative Writing Contest at UNT's Mayborn Literary Nonfiction Conference. First place winner: Eli Saslow, "It Was My Job, and I Didn't Find Him" (The Washington Post), narrates the life of a former officer at the Parkland high school shooting. Second place: Elizabeth Bruenig, "What Do We Owe Her Now?" (The Washington Post), is the story of a high school rape victim who received no justice. Third place: Hannah Dreier, "The Disappeared" (ProPublica), follows a mother who lost her teenage son to gang violence.